Pemberdayaan Masyarakat dalam Usaha Souvenir untuk Meningkatkan Pendapatan Keluarga - Asih, Thorida Nur; Muslihah, Paniti; Fatah, Doni Abdul (Universitas Muhammadiyah Mataram, 2025)
Abstract: One of the efforts that can be made to improve social welfare is through increasing family income. This community service was carried out to increase family income through community empowerment in the cheap souvenir business in Bojonegoro. The method used in this community service activity was training. This community service activity was conducted in three stages: preparation, implementation, and evaluation. The success of the community service was assessed based on the improvement in participants' product packaging skills, as measured by the N-gain index. The results of this community service activity, namely the training, were conducted effectively. The training activities carried out were able to enhance participants' skills and abilities. Participants expressed satisfaction with the training, as assessed through aspects such as the training content, organisers, atmosphere, and materials used during the training.Abstrak: Salah satu upaya yang dapat dilakukan untuk meningkatkan kesejahteraan sosial melalui peningkatan pendapatan keluarga. Pengabdian kepada masyarakat ini dilakukan untuk meningkatkan pendapatan keluarga melalui pemberdayaan masyarakat dalam usaha souvenir murah Bojonegoro. Metode yang digunakan dalam kegiatan pengabdian kepada masyarakat ini adalah training. Kegiatan pengabdian ini dilakukan dalam tiga tahap yaitu, persiapan, pelaksanaan, dan evaluasi. Indikator keberhasilan pengabdian ditinjau dari peningkatan kemampuan peserta dalam pengemasan produk souvenir yang ditinjau dari indeks N-gain. Hasil pengabdian kepada masyarakat ini, yakni pelatihan telah berlangsung secara efektif. Tahapan kegiatan pelatihan yang telah dilakukan dapat meningkatkatkan kemampuan dan keterampilan peserta. Peserta pelatihan merasa puas ditinjau dari aspek materi, panitia, suasana, dan media yang digunakan dalam pelatihan.